Impact of Changes in Criminal-Legal Practices During the COVID-19 Pandemic on the HIV Risk Behaviors of Women Who Use Drugs: Protocol for a Multimethods Qualitative Study - Smoyer, Amy B. (JMIR Research Protocols, 2024)
Background: HIV risk behavior in women who use drugs is related to myriad psychosocial issues, including incarceration. The experience of incarceration elevates women’s HIV risk by disrupting social networks, housing, employment, and access to health care. During the COVID-19 pandemic, changes in criminal-legal practices resulted in decreased incarceration, especially among women. These changes may have largely altered HIV risk among women who use drugs, depending on their access to care in the community. Objective: This study seeks to build knowledge about the impact of shifts in criminal-legal practices during the COVID-19 pandemic on HIV risk behaviors of justice-involved women who use drugs. Methods: Qualitative methods are used to gather and analyze women’s narratives about their life experiences before and during the COVID-19 pandemic, with a focus on individual and structural determinants of HIV risk behaviors. Thirty formerly incarcerated women with a history of substance use are being recruited through collaboration with community partners. Each participant completes a sociodemographic survey and two interviews. The first interview uses a life history instrument that invites participants to reflect on key turning points in their lives. The second interview uses a calendar approach to gather information about participants’ lives during the first year of the COVID-19 pandemic (March 2020-March 2021). The interviews (1 hour each) are audio-recorded and transcribed for analysis. Rapid Qualitative Inquiry and thematic analysis are being used to manage, organize, and interpret the data. The study team will collaborate with a subset of participants to develop digital stories about their COVID-19 experiences, a process that allows for member-checking and triangulation. Findings will be disseminated to program and policy makers in academic venues, community settings, and social service agencies. Results: To date, 10 women’s data have been collected. In total, two themes have been identified in this preliminary data: (1)the chaos and instability of participants’ lives increased during the COVID-19 pandemic: participants reported a wide range of psychosocial and health problems and limited engagement with social service systems. Interaction with criminal-legal systems was rife with uncertainty; participants described living in a state of limbo, which was extremely stressful. (2) When asked to describe a “turning point” in their lives, many participants attributed their substance use to the traumatic loss of a child due to death, incarceration, or termination of parental rights. During the COVID-19 pandemic, participants’ struggles to cope with these unresolved experiences of grief and loss were intensified by the widespread death and dying of the pandemic. Conclusions: Preliminary findings suggest that HIV risk factors increased for participants during the COVID-19 pandemic and invite further investment in community-based harm reduction programs, especially housing, that support women who use drugs. Interventions that address experiences of maternal grief and loss may reduce women’s substance use. Trial Registration:
Keywords: dept.swk; peer-reviewed

Policy Initiatives on Eliminating Anti-Asian Racism - Liu, Meirong; Xu, Yanfeng; Si, Zhanjie (Addressing Anti-Asian Racism with Social Work Advocacy and Action, 2024)
This chapter calls for urgent institutional changes to address structural inequalities through advocacy and legislative action. The authors discuss macro practice methods to address racial injustice through advocacy efforts such as fostering policies eliminating anti-Asian hate and violence, advocating for nondiscriminative policies, improving language access, campaigning for narrative change, building coalitions with social justice groups, encouraging civic engagement, strengthening links with social justice organizations, and promoting policies and programs on Asian American, Native Hawai’ian, and Pacific Islander history education and awareness. Policy advocacy to protect Asian Americans against racial hate crimes is lacking but much needed. Macro social workers’ efforts can pressure policymakers to directly address anti-Asian racism and violence, provide targeted assistance, and call on national, state, and local organizations to ensure investments in culturally appropriate services to Asian American communities.
Keywords: dept.swk

The history of anti-Asian racism and violence in the United States - Liu, Meirong; Lee, Nayoun; Si, Zhanjie; Aquino, Olivia (Addressing Anti-Asian Racism with Social Work Advocacy and Action, 2024)
This chapter begins with a review of the history of anti-Asian racism in the United States. Beginning in the mid-19th century, Asian immigrants played a vital role in the development of the country. However, Asian Americans have faced a long legacy of exclusion and inequality, particularly during periods of economic recession, disease outbreaks, or war throughout US history. Adopting the framework of “othering,” this chapter analyzes the major events in US history related to Asian Americans, such as the Chinese Exclusion Act of 1882, the Immigration Act of 1924, the Japanese internment camps during World War II, and the anti-Asian immigration policies adopted by the Trump administration. Through this, the authors illustrate how historic racism and xenophobia at both individual and institutional levels have operated to marginalize Asian Americans and reproduce inequality, and they demonstrate the common roots of racism that lie in White supremacy.
Keywords: dept.swk

Teaching Note—Antioppressive Pedagogy in Action: The Undergraduate Research Methods Course - Smoyer, A.B.; D’Angelo, K. (Journal of Social Work Education, 2024)
The project of engaging undergraduates in research methods courses is an outstanding challenge for social work educators. Anxiety about the subject is common, for both students and instructors. Further, students’ wariness may reflect historical trauma and their knowledge about the ways in which research has been used to oppress people of color; lesbian, gay, bisexual, transgender, queer or questioning, intersex, asexual or ally, and other sexual and gender minorities communities; and other marginalized populations. This teaching note offers reflections and experiences about developing an undergraduate social work research methods course that uses antioppressive pedagogies to create student-centered learning with experiential team-based activities and ongoing critique about the role of power and privilege in research. Specific teaching resources and strategies are shared. © 2024 Council on Social Work Education.
Keywords: dept.swk

Expanding the notion of personal well-being during covid-19 campus closure in India: results from a mixed-methods study with members of higher education - Yeon, G.; Perumbilly, S.; Elangovan, N.; Awungshi, S.; Varghese, K.J. (Asia Pacific Journal of Educators and Education, 2024)
The COVID-19 pandemic has challenged lives globally in unprecedented ways. While numerous studies have discussed the impact of this pandemic on human lives, this descriptive study examined how this pandemic affected personal well-being (PW) for members of Indian higher education in the early phase of the pandemic in 2020 when there were no vaccines and remedies available. Research participants (n = 551) were faculty members, graduate students, and non-teaching staff in Indian higher education. At the time of data collection, when all campuses were closed, all participants were functioning in their roles in the academic communities via virtual platforms. This descriptive study, based on a mixed-methods research design with concurrent triangulation strategies, collected data from all regions of India. Resulting data identified and discussed the impact of the pandemic on six domains of PW in the life of participants: (a) self-care; (b) professional growth; (c) quality of interrelationship within the family; (d) relationships with significant others outside of the family; (e) process of experiencing/facing and addressing challenges; and, (f) relationship with spirituality/transcendental dimensions. The relevance of the last domain may be unique to Indian participants’ socio-cultural context and ethos. The findings and discussion explain how PW is a composite of all these six domains, and the pandemic expanded the notion of PW for the members of Indian higher education. Further, the findings also provided a general orientation on how educational leadership teams and institutions can enhance at least three specific dimensions of their community members and thus increase the likelihood of improving the quality of their professional and personal life. The findings may also have relevance for academic communities worldwide and inform clinicians working with members of academic communities, educational institutions, and policymakers. © Penerbit Universiti Sains Malaysia, 2024.
Keywords: Teacher leadership; dept.mft; distributed leadership; middle leaders; middle leadership; peer-reviewed; teacher leaders

Bridging the gap between spirituality and mental health: the need for trauma-informed ministries within Latino communities - Hernandez, V. (Journal of Religion and Spirituality in Social Work, 2024)
The impact of trauma on mental health has led to the increased development of trauma-informed organizations. Little is known, however, about the benefits of using a trauma-informed care perspective within a faith-based setting, particularly among Latino communities. This article reviews the literature and identifies gaps suggesting the problem of a lack of mental health and trauma-informed awareness among places of worship. The need for developing trauma-informed ministries within places of worship is recommended to assist in promoting the psychological, emotional, and spiritual well-being of congregants and community members within faith-based settings. © 2024 Taylor & Francis.
Keywords: Latino; Mental illness; dept.swk; ministry; peer-reviewed; training; trauma-informed

Promoting food justice and the right to adequate food in social work education - Hall-Faul, M.; D’Angelo, K.A.; Libal, K. (Journal of Human Rights and Social Work, 2024)
Food justice is centered on the principle that food is a basic human right. Despite a mandate to include human rights and social justice content in the social work curriculum, food insecurity and food justice receive scant attention in social work academia. Food insecurity affects a substantial portion of the population, with a disproportionate impact on women and Black, Latinx, and Native American communities. A human rights-based approach to food requires more than access to food; it demands that food also be available, adequate, and culturally acceptable. A right to food framework also calls on policymakers to immediately address disparities in food security, which are prevalent in the USA due to historical and ongoing systemic racism. This paper provides a conceptual understanding of food justice and its historical connections to social work, outlines the requirements of a right to food, and concludes by offering strategies to integrate food justice into the micro, mezzo, and macro social work curriculum. © 2024, The Author(s), under exclusive licence to Springer Nature Switzerland AG.
Keywords: Food insecurity; Food justice; Human rights; Hunger; Right to food; Social work; Social work education; dept.swk; peer-reviewed

Desire on the Inside: Incarcerated bisexual women, identity, and human connection - Smoyer, Amy; Harvey, Rebecca (Queering Desire: Lesbians, Gender and Subjectivity, 2024)
Queering Desire explores, with unprecedented interdisciplinary scope, contemporary configurations of lesbian, bi, queer women’s, and non-binary people’s experiences of identity and desire. Taking an intersectional feminist and trans-inclusive approach, and incorporating new and established identities such as non-binary, masculine of centre (MOC), butch, and femme, this collection examines how the changing landscape for gender and sexual identities impacts on queer culture in productive and transformative ways. Within queer studies, explorations of desire, longing, and eroticism have often neglected AFAB, transfeminine, and non-binary people’s experiences. Through 25 newly commissioned chapters, a diverse range of authors, from early career researchers to established scholars, stage conversations at the cutting edge of sexuality studies. Queering Desire advances our understanding of contemporary lesbian and queer desire from an inclusive perspective that is supportive of trans and non-binary identities. This innovative interdisciplinary collection is an excellent resource for scholars, undergraduate, and postgraduate students interested in gender, sexuality, and identity across a range of fields, such as queer studies, feminist theory, anthropology, media studies, sociology, psychology, history, and social theory. In foregrounding female and non-binary experiences, this book constitutes a timely intervention.
Keywords: dept.mft; dept.swk; peer-reviewed

Teaching Note—Innovating the Curriculum: Bringing History Back Into Social Work Education - Abramovitz, Mimi; Curran, Laura; Harty, Justin S.; Toft, Jessica; Tomczak, Stephen Monroe (Journal of Social Work Education, 2024)
History, the major storehouse of information, informs us about the important relationship between people and society and increases our understanding of basic societal values and institutional arrangements. A recent New York Times op-ed described “The Dangerous Decline of the Historical Profession.” Likewise for historical content in social work education, exacerbated by the 1970s‘ rise of neoliberalism and the profession’s long marginalization of historical research and teaching. The Social Welfare History Group renews its call to bring historical content back into social work education and to correct its deep-seated race, class, gender, and colonizing distortions. To ensure that all social work courses include history, we can revive the value historical knowledge; prepare a cadre of historical researchers and instructors; financially support emerging scholars and develop a pipeline of history-informed faculty to teach the next generation of social workers.
Keywords: dept.swk; peer-reviewed